COPD An Update in Pathogenesis and Clinical Management - McCarthy, Cormac (IntechOpen, 2018)
Chronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide and is estimated to become the third most common cause of death over the next decade. The knowledge of COPD pathogenesis and the disease course has greatly improved this progression in understanding and continues to have significant implications in the management of this condition. Novel areas of interest in COPD pathogenesis include further development of animal models, a better understanding of the genetics and epigenetics, the role of the microbiome, and an increasing appreciation of the associated comorbidities. This book intends to provide the reader with a brief overview of these topics and also provide an in-depth review of the current nonpharmacological clinical approaches to managing patients with COPD.